Konsep Istikhlaf dalam Etika Bisnis Islam - Nurhasanah, Nurhasanah; Arfah, Arfah; Olfa, Ein Maria (AL-Muqayyad, 2023)
This research aims to examine the concept of istikhlaf in business ethics and what impact it has on business people. This research is of the type of library research or library research using qualitative methods by carrying out content analysis using the Content Analysis model. The results of the research show that the concept of istikhlaf is related to divinity, prosperity and justice. Business people must have fundamental attitudes/ethics and character, namely honest, trustworthy, informative, intelligent and intellectual, professional, motivational, critical, communicative, disciplined, fighting, innovative, adaptive and committed. Business actors are prohibited from behaving Al-bathil, Al-Fasad, Al-Zhalim which can cause imbalance and injustice in business. In this way, the character contained in istikhlaf influences behavior, so that it can reduce or even eliminate/inhibit negative behavior and bad ethics in business people. By embedding istikhlaf in business people, good, wise behavior, loss of selfish attitudes, more tolerance, careful use of assets (not causing waste), careful in policies so that the business game will be safer and more peaceful, competitive fair, and become a social homo economicus, not a lupus homo homini.